Penerapan Konsep Desentralisasi pada Pelayanan Publik: Studi Kebijakan Pengelolaan Municipal Solid Waste di Jepang - Vanya, Irwinda; Nursadi, Harsanto (Universitas Ekasakti, 2023)
In theory, decentralization is believed to have a good impact on improving public services. Japan is one of the countries that has succeeded in providing public services through granting authority to local governments. This paper discusses the application of the concept of decentralization to public services, particularly municipal solid waste management policies in Japan. The research was conducted on the Japanese government's policy regarding municipal solid waste management. The research method used is normative juridical. The results of the study show that community involvement, dynamic partnerships and funding creativity are the keys to the successful application of the concept of decentralization in municipal solid waste management in Japan. This shows a shift in the meaning of decentralization and the use of New Public Service, New Public Management and New Public Governance perspectives in the application of the concept of decentralization in municipal solid waste management in Japan. The Japanese government defines decentralization as a multidimensional process. To benefit from decentralization, lawmakers need to formulate appropriate configurations and relationships between stakeholders.